"Airway Pressure Release Ventilation" a step up care in ARDS (Bangladesh Critical Care Journal, 2014)
APRV is a mode of mechanical ventilator which uses the principal of open lung approach. It is thought to be an effective & safe alternative for difficult to oxygenate patients like ARDS. It is inverse ratio, pressure controlled, intermittent mandatory ventilation with unrestricted spontaneous breathing. APRV has many purported advantages over conventional ventilation including alveolar recruitment, improved oxygenation, preservation of spontaneous breathing, improved hemodynamics and potential lung-protective effects. It has many claimed disadvantages related to risks of volumtrauma and increased energy expenditure related to spontaneous breathing. Though it was first described more than 20 years ago still it has not gained popularity till date as it is yet to prove its mortality benefits over other conventional modes. Currently there is a lot of ongoing trial globally on it. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19955 Bangladesh Crit Care J March 2014; 2 (1): 35-37